Customer Satisfaction in Nepalese Cellular Networks - Dahal, Rewan Kumar (Tribhuvan University Journal, 2019)
Now a days identification of responsible factors that influence customer satisfaction is a key concern of marketers and research scholars and it will remain in future too. The purpose of the study was to identify the responsible factors that affect on customer satisfaction with cellular networks in Nepal and analyze them. Nepal Telecom and Ncell were taken as sample organizations where they occupy more than 94 % of market share. The study was based on primary data collected through a structured questionnaire based on the judgmental sampling technique from 816 customers. It examined that price and service quality, brand and loyalty, corporate social responsibilities, network and coverage, and customer care and innovation were the responsible factors in the assessment of customer satisfaction with Nepalese cellular networks services. The study concluded that mobile service providers should concentrate upon the factors responsible on customer satisfaction and care of those factors that have significant influence on promoting customer satisfaction in Nepalese cellular networks industry.